2001
DOI: 10.1149/1.1380674
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Chromate Ions with Surface Intermetallics on Aluminum Alloy 2024-T3 in NaCl Solutions

Abstract: The aim of this paper is to analyze the interaction of chromate ions with surface intermetallics on Al 2024-T3 in NaCl media under open circuit conditions at pH 3 and 6. These interactions are probed by Auger electron ͑AES͒, X-ray photoelectron, and energy dispersive X-ray spectroscopies, as well as scanning electron microscopic techniques. In acidic NaCl solution, S-phase particles undergo bulk dealloying through preferential dissolution of magnesium and aluminum, which leaves the particles enriched in copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 25 publications
(43 reference statements)
8
43
0
1
Order By: Relevance
“…AES studies have shown that a chromium-rich (Cr III -Cr VI ) film forms on the entire surface of AA2024-T3, but preferentially on the Al 2 CuMg inclusions, when chromate is added to the sodium chloride solution. 19,20 It was suggested that chromate strongly inhibits magnesium dissolution and prevents copper redeposition on the bulk matrix, which is in agreement with our data.…”
Section: Resultssupporting
confidence: 92%
“…AES studies have shown that a chromium-rich (Cr III -Cr VI ) film forms on the entire surface of AA2024-T3, but preferentially on the Al 2 CuMg inclusions, when chromate is added to the sodium chloride solution. 19,20 It was suggested that chromate strongly inhibits magnesium dissolution and prevents copper redeposition on the bulk matrix, which is in agreement with our data.…”
Section: Resultssupporting
confidence: 92%
“…The interest in CO adsorption is mainly due to the detrimental role of adsorbed carbon monoxide in electrocatalysis, where it often acts as a poisoning intermediate that blocks active surface sites. This blocking effect, however, can be positive in other cases, for example in corrosion, a field that has also attracted Wieckowski's attention [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Various analytical techniques have been used to study the chemical and structured nature of the CCC formed on Al-Cu alloy, including x-ray photoelectron spectroscopy (XPS), 5,7,25,26 x-ray absorption near-edge structure (XANES) spectroscopy, 10,18 -20,27 secondary ion mass spectrometry (SIMS) 28 and Fourier transform infrared (FTIR) and Raman spectroscopy. 1,24,29 -31 Several studies have shown that the CCC is inhomogenously distributed on the AA2024-T3 surface and that the underlying microstructure induces spatial and depth composition heterogeneity in the CCC.…”
Section: Introductionmentioning
confidence: 99%